2023
DOI: 10.5415/apallergy.0000000000000005
|View full text |Cite
|
Sign up to set email alerts
|

The epithelial barrier theory: development and exacerbation of allergic and other chronic inflammatory diseases

Abstract: It is now longer than half a century, humans, animals, and nature of the world are under the influence of exposure to many newly introduced noxious substances. These exposures are nowadays pushing the borders to be considered as the causative or exacerbating factors for many chronic disorders including allergic, autoimmune/inflammatory, and metabolic diseases. The epithelial linings serve as the outermost body’s primary physical, chemical, and immunological barriers against external stimuli. The “epithelial ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 158 publications
0
8
0
Order By: Relevance
“…Aeroallergen sensitization occurs when an allergen enters the nasal mucosal epithelial barrier and is processed by antigen-presenting cells (eg, dendritic cells), causing differentiation of naive T cells to T-helper type 2 cells that are capable of releasing cytokines (eg, IL-4, IL-5, IL-13) . This process promotes B-cell production of IgE specific to the allergen, which binds to high-affinity IgE receptors on mast cells, Langerhans cells, monocytes, and basophils.…”
Section: Discussionmentioning
confidence: 99%
“…Aeroallergen sensitization occurs when an allergen enters the nasal mucosal epithelial barrier and is processed by antigen-presenting cells (eg, dendritic cells), causing differentiation of naive T cells to T-helper type 2 cells that are capable of releasing cytokines (eg, IL-4, IL-5, IL-13) . This process promotes B-cell production of IgE specific to the allergen, which binds to high-affinity IgE receptors on mast cells, Langerhans cells, monocytes, and basophils.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, people with CD who are not diagnosed in time are at risk of developing alterations in intestinal permeability, resulting from a failure of the epithelial barrier. This dysfunction may be influenced by genetic factors, alterations in the microbiota, environmental exposures and allergens, as well as by complex cellular and molecular mechanisms [23]. In addition, it has also been suggested that the accumulation of factors harmful to the epithelial barrier, due to industrialization and modern lifestyles, is contributing to the growing prevalence of this disease [24].…”
Section: Discussionmentioning
confidence: 99%
“…2 ). A leaky barrier enables the microbiome's translocation from the periphery to inter-epithelial and even deeper sub-epithelial areas [ 18 ].…”
Section: The Epithelial Barrier Theorymentioning
confidence: 99%
“…This series of events lead to persistent leakiness of barriers and inflammation of the peri-epithelial areas, dysbiosis, opportunistic pathogen colonization and defective barrier healing, all of which could be an explanatory mechanism for allergic disorders and other many immune-related inflammatory diseases (Fig. 2 ), [ 9 ••, 10 , 18 ].
Fig.
…”
Section: Introductionmentioning
confidence: 99%